CHARACTER BUILDING PENDIDIKAN KARAKTER - Ade Chita Putri Harahap (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2019)
Character education is one thing that must be considered at this time, especially in educational institutions. Educational institutions are responsible for assisting students in understanding, paying attention and doing good ethical values. Character education is emphasized on the development of good moral values, ethics, manners so that it can be applied in daily life for students.Keywords: Character education, ethics, courtesy, courtesy